Adjuvant therapy for renal cell carcinoma, finally a new standard? - Renner, Alex; Rojas, Carlos; Walton-Diaz, Annerleim; Burotto, Mauricio (Frontiers in Oncology, 2022)
Localized renal cell carcinoma (RCC) has the potential to be cured with surgery alone, however some patients have a high risk of relapse and may benefit from additional treatment. Several efforts have been made to identify effective strategies, with mostly negative results. However, recent results with immune checkpoint inhibitors may change the current standard, and several ongoing trials are exploring new alternatives. In this perspective we aim to provide an overview of previous adjuvant therapy efforts, current data supporting the use of checkpoint blockade, as well as a future outlook for adjuvant therapy in renal cell carcinoma.